The Importance Of Maritime Transport In Developing Tourism Activities In Algeria - Bourouis ,Abdelali (University of Eloued جامعة الوادي, 2025)
The importance of transport has increased as a supporting factor for the image of the tourist destination, providing a successful tourism base, which is defined as a driver of economic activity and social development. Tourism in Algeria has experienced weak and fluctuating growth rates over the past ten years, but recorded some improvement in 2023 due to enhancements in transport and the development of supporting infrastructure. The purpose of this paper is to demonstrate the importance of maritime transport in developing tourism activity, as the development of tourism in Algeria depends on the enhancement of transportation systems in all its forms, especially maritime transport. Therefore, the focus is on analyzing tourism indicators in Algeria, along with the development of land, air, and maritime tourist transport. Furthermore, it discusses the significance of the ENTMV maritime transport company for passengers in enhancing Algeria's competitiveness as a tourist destination and its impact on developing tourism activity, highlighting its substantial role that it can play in this field. This study acknowledges the important role of ENTMV (The maritime passenger transport company) in developing tourism activities; however, it has been shown that it plays a modest role in tourism transport compared to the services provided by the air transport and land transport sectors. It has also been revealed that it faces numerous challenges that hinder its ability to meet the increasing demand for tourism transport and that it requires comprehensive development of its legal, regulatory, and human systems, as well as the modernization of its fleet and commercial networks, in order to implement the new maritime transport policy established by the government.
مقال
Keywords: Transport; Tourism; Tourist transport; Maritime transport for passengers; ENTMV.